Quasi-Analytical Model for Space-Time Periodic Structures Controlled by Diodes - Sánchez-Martínez, Juan Rafael; Pérez-Escribano, Mario; Alex-Amor, Antonio; Padilla, Pablo; Molero, Carlos (My University, 2025)
This paper presents a technique to model time-varying periodic structure with two axis of spatial periodicity, x̂ and ŷ. The model is based on circuit-approach techniques, where the knowledge, a priori, of the field at the discontinuity is necessary. Time modulation is invoked via diodes. The fields when the diodes are in ON or in OFF states are extracted from a commercial software. A smart combination of these fields give rise to the space-temporal profile, leading to the resolution of the whole electromagnetic field in the regions surrounding the structure.
Keywords: Materiales nanoestructurados; Time varying; Space-time; Metasurface; Circuit model; Periodic structure